Cytotoxicity test pentacyclic triterpenes of Eupatorium inulifolium HBK on myeloma cells and their docking study - Sri Mulyani Mulyadi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
A test of cytotoxic activity of pentacyclic triterpenes 12,13-Dihydro-1-α-amirin-20,30-en-3-acetate and12,13-Dihydro-α-amirin-20,30-en-3ol compounds on myeloma cells and their docking has been conducted. Two compounds were treated on myeloma cells which their cells densities have been determined. They were subsequently incubated with a series of compound dosage from 2000 µg/mL to 125 µg/mL. This research aims to determine the level in which both the compounds influence the myeloma cells using MTT method (reactor 3-(4,5-Dimetiltiazol-2-il)-2,5-difenil tetrazollium bromide) and their docking that react to receptor 1XKK. Activity of compounds on myeloma cell after 24 hour incubation has shown that the values of IC50 for 12,13-Dihydro-α-amirin-20,30-en-3-acetate and 12,13-Dihydro-α-amirin-20,30-en-3ol are 0.428 mM and 1.515 mM, respectively. In this research, doxorubicin is used as a positive control. The IC50 value of doxorubicin is 6.896 x 10-5 µg/mL. Results show that docking score for 12,13-Dihydro-α-amirin-20,30-en-3-acetat to Epidermal Growth Factor Receptor (1XKK) is -78.9662 (7). Meanwhile, docking score for 12,13-Dihydro-α-amirin-20,30-en-3-ol to Epidermal Growth Factor Receptor(1XKK) is -74.1941 (10). Doxorubicin docking score is -86.6585 (2). From the results, it can be inferred that the two compounds have cytotoxic activities with bigger IC50 than the doxorubicin as positive control. In order to obtain more potent cytotoxic activity, the coumpound has to be modified and tested and then docked using receptor Epidermal Growth Factor Receptor.Keywords:cytotoxic activity; EGFR; myeloma cells; 12,13-Dihidro-α-amirin-20,30-en-3-asetat dan 12, 13-Dihidro-α-amirin-20,30-en-3-ol